Sparing Nature : The Conflict between Human Population Growth and Earth's Biodiversity - McKee, Jeffrey Kevin (Book collections on Project MUSE., 2003)
Are humans too good at adapting to the earth's natural environment? Every day, there is a net gain of more than 200,000 people on the planet-that's 146 a minute. Has our explosive population growth led to the mass extinction of countless species in the earth's plant and animal communities? Jeffrey K. McKee contends yes. The more people there are, the more we push aside wild plants and animals. In Sparing Nature, he explores the cause-and-effect relationship between these two trends, demonstrating that nature is too sparing to accommodate both a richly diverse living world and a rapidly expand.